Exchange rate pass-through in the euro area and EU countries - Eva Ortega; Chiara Osbat (European Central Bank (ECB), 2020)
Aggregate exchange rate pass-through (ERPT) to import and consumer prices in the EU is currently lower than it was in the 1990s and is non-linear. Low estimated aggregate ERPT to consumer prices does not at all mean that exchange rate movements do not have an impact on inflation, as aggregate rules of thumb mask substantial heterogeneities across countries, industries and time periods owing to structural, cyclical and policy factors. Looking also at new micro evidence, four key structural characteristics explain ERPT across industries or sectors: (i) import content of consumption, (ii) share of imports invoiced in own currency or in a third dominant currency, (iii) integration of a country and its trading partners in global value chains, and (iv) market power. In the existing literature there is also a robust evidence across models showing that each shock which causes the exchange rate to move has a different price response, meaning that the combination of shocks that lies behind the cycle at any point in time has an impact on ERPT. Finally, monetary policy itself affects ERPT. Credible and aggressive monetary policy reduces the observed ex post ERPT, as agents expect monetary policy to counteract deviations of inflation from target, including those relating to exchange rate fluctuations. Moreover, under the effective lower bound, credible non-standard monetary policy actions result in greater ERPT to consumer prices. This paper recommends moving away from rule-of-thumb estimates and instead using structural models with sufficient feedback loops, taking into account the role of expectations and monetary policy reactions, to assess the impact of exchange rate changes when forecasting inflation.
Keywords: C50; E31; E52; F31; F41; 330; exchange rates; import prices; consumer prices; inflation; pass-through; euro area; monetary policy